Point of Care (POC) Influenza Immunization for Pregnant Women, Calgary Zone, Alberta Health Services. (2018) - Manji, Sofiya; McDonald, Sheila; Metcalfe, Amy; Nerenberg, Kara; Zhang, Jing; Castillo, Eliana
No abstract available